POLIGAMI DAN PROSEDURNYA MENURUT HUKUM PERKAWINAN DI INDONESIA - Muhammad Fikri Akbar (MAQASHIDUNA: Jurnal Hukum Keluarga Islam, 2025)
Polygamy is one form of marriage permitted in Islam, as regulated in Surah An-Nisa verse 3. Islam states that a man is allowed to marry up to four women, with the main requirement being the ability to “act justly.” Polygamy is not obligatory, but it is permitted under certain conditions, such as when “the wife is unable to fulfill her duties, suffers from an incurable illness, or cannot bear children.” In Indonesian positive law, polygamy is regulated by Law Number 1 of 1974 on Marriage, the Compilation of Islamic Law (KHI), and government ermitted if there is “consent from the wife, the husband's financial ability to provide for the household, and assurance that he will act justly, as well as obtaininregulations for Civil Servants. The law stipulates that polygamy is only pg permission from the Religious Court.” Without such permission, “the marriage is declared to have no legal force.” This study explores the meaning of polygamy, its legal basis, and the requirements and procedures that must be fulfilled for polygamy to be valid under both Islamic law and Indonesian positive law. In practice, polygamy conducted without legal procedures may lead to problems such as the legal status of the second wife, the children, inheritance rights, and potential legal violations. Therefore, understanding legal provisions is crucial before engaging in polygamous marriage.